Difference in Pathomechanism Between Crohn's Disease and Ulcerative Colitis Revealed by Colon Transcriptome. Issue 4 (4th December 2018) - Yang, Lili; Tang, Shijie; Baker, Susan S; Arijs, Ingrid; Liu, Wensheng; Alkhouri, Razan; Lan, Ping; Baker, Robert D; Tang, Zhipeng; Ji, Guang; Rutgeerts, Paul; Vermeire, Severine; et al.
Abstract: Background: We aim to identify the differences in colonic mucosal transcriptome between Crohn's disease (CD) and ulcerative colitis (UC) for a better understanding of the molecular pathology. Methods: Differentially expressed genes (DEG) in the colonic mucosa of CD and UC were identified with a global gene expression microarray dataset generated from the colon biopsies of CD and UC patients and normal controls. The DEGs were then processed to identify altered pathways and modularized DEGs and pathways. Quantitative real-time polymerase chain reaction (qRT-PCR) analysis with an independent cohort of samples was performed to validate the microarray data. Results: At the pathway level, virus infection and autoimmune pathways were upregulated in CD but not in UC when compared with controls. Some of the relevant DEGs (such as TAP1 and TAP2) were elevated in both CD and UC, with CD exhibiting more pronounced elevations. Gene expression levels in viral infection pathways were correlated with those of autoimmune pathways. In contrast, pattern recognition–mediated innate immune pathways (TLR4 and TLR2) were significantly elevated in UC but not in CD. Similar results were observed with an independent cohort by qRT-PCR. Conclusions: Our data support the hypothesis that viral infection induced autoimmunity may represent a pathomechanism for IBD, especially CD. However, pattern recognition–mediated innate immunity targeting microbiome may play a more important role in UC compared with CD. Our findings identified different intervention targets for CD and UC, which may lead to more effective treatments for IBD patients.